Tailored phase transition temperature and negative thermal expansion of Sc-substituted Al2Mo3O12 synthesized by a co-precipitation method. Issue 7 (6th June 2019) - Liu, Hongfei; Sun, Weikang; Zhang, Zhiping; Zhang, Xiuyun; Zhou, Yuxue; Zhu, Jun; Zeng, Xianghua
Abstract : Sc 3+ substitution reduces the T c of Al2 Mo3 O12 and makes it show stable negative thermal expansion in a wider temperature range. Abstract : Scandium-substituted Al2 Mo3 O12 ceramics corresponding to the general formula Al2− x Sc x Mo3 O12 (0 ≤ x ≤ 0.5) were fabricated by the co-precipitation reaction. Sc 3+ is proved to successfully replace Al 3+ and reduces the average grain size of the Al2− x Sc x Mo3 O12 ceramics from 6 μm to 1 μm. Sc 3+ substitution induces a crystal structure change from monoclinic to orthorhombic symmetry. When the Sc 3+ substitution content ( x ) is <0.4, Al2− x Sc x Mo3 O12 ceramics crystalize in a monoclinic structure and exhibit positive thermal expansion, while when x ≥ 0.4, the Al2− x Sc x Mo3 O12 ceramics crystalize in an orthorhombic structure and display negative thermal expansion (NTE), indicating that the phase transition temperature of Sc 3+ -substituted Al2 Mo3 O12 ceramics can be successfully reduced from 204.8 °C to room temperature with increasing substituted Sc 3+ content. Orthorhombic Al1.6 Sc0.4 Mo3 O12 shows stable NTE above room temperature. Its coefficient of thermal expansion is −2.02 × 10 −6 °C −1 from 25 °C to 500 °C. The theoretical calculation result also accords well with the above experimental data.